Overview of Risk Factors for Toddlers with Congenital Heart Disease Suffering from Pneumonia at Dr. M. Djamil General Hospital, Padang, Indonesia - Ricco Azali; Didik Hariyanto; Finny Fitry Yani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Congenital heart disease (CHD) includes structural and non-structural abnormalities that arise from birth. Disorders of the circulatory system can also affect the respiratory system, causing symptoms and disturbances that similar to primary respiratory disease. This study aimed to describe the risk factors for toddlers with congenital heart disease who suffer from pneumonia at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: Descriptive observational study using secondary data. A total of 58 research subjects participated in the study. The research subjects met the inclusion criteria in the form of patients who had been diagnosed with congenital heart disease, aged 29 days – 60 months, and were treated at Dr. M. Djamil General Hospital, Padang, Indonesia. Data analysis was performed using SPSS software univariately. Results: The majority of patients with various age levels have a cured outcome. The majority of subjects with medium and high parental education had a greater recovery percentage than subjects with low parental education. Subjects with medium and high socioeconomic status had a greater percentage of recovery outcomes than subjects with low socioeconomic status. The majority of subjects with normal nutritional status and normal birth weight had a higher percentage of recovered outcomes than those who died. The history of DPT immunization and the type of congenital heart disease did not show a large percentage difference between patients who recovered and died. History of measles immunization and leukocytosis showed a greater percentage of patients with cured outcomes than death outcomes. Conclusion: CHD patients with pneumonia are under 1 year old, male, come from families with low-medium socioeconomic status, low-medium educational level, and malnutrition status have worse patient outcomes.